Given that is a real number, that is find the value of that satisfies the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
y + y 2 + y 3 + … + y 6 0 + y 6 1 = − 1 y 6 1 + y 6 0 + y 5 9 + y 5 8 + … + y 3 + y 2 + y + 1 = 0 y 6 0 ( y + 1 ) + y 5 8 ( y + 1 ) + … + y 2 ( y + 1 ) + 1 ( y + 1 ) = 0 ( y + 1 ) ( y 6 0 + y 5 8 + … + y 2 + 1 ) = 0
The first factor:
y + 1 = 0 ⟹ y = − 1
The second factor:
y 6 0 + y 5 8 + … + y 2 + 1 = 0
Notice that for even positive integers of n , y n ≥ 0 for all real values of y
This implies that y 6 0 ≥ 0 , y 5 8 ≥ 0 , … , y 2 ≥ 0
Therefore,
y 6 0 + y 5 8 + … + y 2 ≥ 0 y 6 0 + y 5 8 + … + y 2 + 1 ≥ 1
From this, we can conclude that the second factor has no real roots.
Therefore, the only real solution is y = − 1